Maqashid al-Sharia in the Study of Hadith and its Implication for the Renewal of Islamic Law: Study on Jasser Auda’s Thought - Ahmad Syafi'i Sulaiman Jamrozi; Suad Fikriawan; Syamsul Anwar; Misnen Ardiansyah (Justicia Islamica, 2022)
This article examines Jasser Auda's maqashid approach to studying hadith and its implications for the renewal of Islamic law. Generally speaking, one way to better understand the purpose of the hadith is through contextualizing the Prophetic narrations (hadith), primarily when the scripture cannot be understood textually. Using a descriptive-analytic and critical approach, this study showed that the conception of Auda’s maqashid could solve the problem. First, in these terms, Auda offers a way of reading the scripture based on the intent in applying Islamic law and its implications when maqashid is a primary consideration in reading and applying the law. Second, the theoretical approach as a result of Auda's academic research is the validation of several ijtihad methodologies which will practically produce the Anthropocentric Maqashid, namely the Maqashid model considering the development of world governance thinking within the framework of nation-states on the one hand, and making human values such as freedom, equality, justice, democracy as a source of maslahah on the other. The logical consequence of this Anthropocentric Maqashid idea necessitates drawing legal conclusions (istinbath al-ahkam) based on maslahah, no longer on the text.